(3Yde GdHjGf (B:s (3OQGSI JMdjdjI deSGFd GdHjGf (B/s - (3ajhO, HSjhfj YHO GdaJGM HSjhfj,s 1950- ((3GdbGgQI (B:s (3eDSSI GdeNJGQ,s, 2011)
(3jhVM gPG GdcJGH eSGFd GdHjGf hJLdjJgG hJMdjd ThGgOgG(B.s
(3HHdjhLQGajI (B: (3U(B. 275-278.s
Keywords: (3GddZI GdYQHjIs -- (3HdGZIs